PENGARUH PUPUK HAYATI CAIR TIENS GOLDEN HERVERST TERHADAP PERTUMBUHAN BIBIT TANAMAN CENGKEH (Eugenia aromatica L.) - Josina Irene Brigetha Hutubessy (AGRICA, 2014)
The study aims at revealing the impact of Tiens Golden Harvest organic liquid fertilizer on the growth and the yield of clove seed and optimum dose of Tiens Golden Harvest liquid fertilizer leading to the growth and the optimal yield of clove seed. The design used in this study was random block design with the treatment of T0 = Tiens Golden Harvest fertilizer 0 g/seed T1 = Tiens Golden Harvest 45 ml/seed, T2 = Tiens Golden Harvest fertilizer 90 ml/seed, T3 = Tiens Golden Harvest fertilizer 135 ml/seed, T4 = Tiens Golden Harvest fertilizer 180 ml/seed. Observation variables in this study were plant height, total leaves, leaf width, total fresh weight of brangkasan plant-1 and total dry oven weight of plant-1. The analysis result indicated that giving a different dose of Tiens Golden Harvest fertilizer may impact the plant height of 44,27%, fresh weight of plant-1of 32,58%, dry oven weight of plant-1of 48,92%. The optimum dose of Tiens Golden Harvest fertilizer contributing to the optimal growth of the clove seed is 180ml seed-1.